Chronic CD40L blockade is required for long-term cardiac allograft survival with a clinically relevant CTLA4-Ig dosing regimen - Unger, Lukas W.; Muckenhuber, Moritz; Mahr, Benedikt; Schwarz, Christoph; Pilat, Nina; Granofszky, Nicolas; Regele, Heinz; Wekerle, Thomas (Frontiers in Immunology, 2022)
In de-novo kidney transplantation, the CTLA4-Ig fusion protein belatacept is associated with improved graft function but also an increased risk of acute rejection compared to calcineurin inhibitor therapy. The combination with a second costimulation blocker could potentially improve outcome while avoiding calcineurin inhibitor toxicity. The aim of this study was to define the conditions under which the combination of CTLA4-Ig and CD40L blockade leads to rejection-free permanent graft survival in a stringent murine heart transplantation model. Naïve wild-type or CD40L (CD154) knock-out mice received a fully mismatched BALB/c cardiac allograft. Selected induction and maintenance protocols for CTLA4-Ig and blocking αCD40L monoclonal antibodies (mAB) were investigated. Graft survival, rejection severity and donor-specific antibody (DSA) formation were assessed during a 100-day follow-up period. Administering αCD40L mAb as monotherapy at the time of transplantation significantly prolonged heart allograft survival but did not further improve the outcome when given in addition to chronic CTLA4-Ig therapy (which prolongs graft survival to a median of 22 days). Likewise, chronic αCD40L mAb therapy (0.5mg) combined with perioperative CTLA4-Ig led to rejection in a proportion of mice and extensive histological damage, despite abrogating DSA formation. Only the permanent interruption of CD40-CD40L signaling by using CD40L-/- recipient mice or by chronic αCD40L administration synergized with chronic CTLA4-Ig to achieve long-term allograft survival with preserved histological graft integrity in all recipients without DSA formation. The combination of α-CD40L and CTLA4-Ig works most effectively when both therapeutics are administered chronically.